The importance of neighborhood type dissonance in understanding the effect of the built environment on travel behavior - Manaugh, Kevin; El-Geneidy, Ahmed (Journal of Transport and Land Use, 2015)
For many years, researchers have struggled to separate the effects of personal tastes—including residential choices—from built environment and transport related factors when attempting to understand and model travel behavior. This paper will briefly describe how issues related to self-selection, if not controlled for in a travel behavior analysis, can lead to over- and under-estimation of the effect of the built environment on travel behavior. A theoretical model is presented, which is followed by an empirical analysis based on survey data capturing residential choice factors to test our theory. Our analysis shows that by separating people that have chosen their current home location based primarily on transport-related concerns from people who have located based primarily on housing and neighborhood characteristics, we are able to gain a nuanced understanding of how various “costs” associated with using public transit (access time, waiting time, and transfers) affect the likelihood of taking transit. We find a strong aversion to transfers as well as different responses to these factors based on reasons for living in a given location. We demonstrate how model predictions vary greatly especially when self-selection factors are included in the analysis. Findings from this research shed light on the importance of self-selection in travel behavior research, giving transport planners and engineers clear examples how ignoring these factors can lead to misleading findings.